2019
DOI: 10.1371/journal.pone.0223655
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents living with HIV are at higher risk of death and loss to follow up from care: Analysis of cohort data from eight health facilities in Ethiopia

Abstract: BackgroundThere are limited data on the treatment outcomes of adolescents living with HIV. Our objective was to compare mortality and loss to follow up (LTFU) rates between adolescent and younger age groups at enrollment in care.MethodsThis was a retrospective cohort study carried out in eight health facilities in two regions of Ethiopia. Adolescents (age 10–14 and 15–19 year) and children (age 0–9 year) enrolled in chronic HIV care between 2005 and 2013 constituted the study population. We reviewed the indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
54
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 24 publications
8
54
5
Order By: Relevance
“…Finally, we found that adherence to treatment was a challenge in this cohort. This is consistent with literature regarding ALWH that demonstrate poor rates of adherence to treatment [70][71][72]. While this pilot study did not aim to assess the impact of our intervention on medication-taking, many participants reported that the WhatsApp ® groups helped them improve their adherence by establishing a peer support network.…”
Section: Discussionsupporting
confidence: 85%
“…Finally, we found that adherence to treatment was a challenge in this cohort. This is consistent with literature regarding ALWH that demonstrate poor rates of adherence to treatment [70][71][72]. While this pilot study did not aim to assess the impact of our intervention on medication-taking, many participants reported that the WhatsApp ® groups helped them improve their adherence by establishing a peer support network.…”
Section: Discussionsupporting
confidence: 85%
“…There are several factors that might explain the higher mortality observed among adolescents. Previous studies have attributed these differences to structural barriers, such as restrictive laws on the age of consent for self‐care, poor linkage to CTC care and poor adherence to ART [ 15 , 23 ]. Despite the known need for protection from HIV infections and other reproductive health risks, their age and social and economic statuses limit the access of adolescents to information and services, which can lead to poor outcomes, including mortality [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published data indicate that some adolescents and young adults living with HIV may die within the first year of ART initiation [ 10 , 11 , 12 , 13 ]. The predictors of mortality among adolescents and young adults living with HIV are not uniform across studies [ 7 , 14 , 15 , 16 ]. Identified predictors include low CD4 count, advanced WHO Stage clinical disease, short duration of ART, sex and age [ 7 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, suboptimal ART adherence is common among adolescents with HIV. While there is an overall improvement in other age groups in the epidemic control of HIV, when compared with other age categories [ 3 ], adolescents are characterized by (1) higher treatment dropout rate [ 4 , 5 ], (2) lower viral suppression achievement [ 6 ], (3) rising AIDS-related illnesses [ 5 ], and (4) a smaller decrease in AIDS-related deaths.…”
Section: Introductionmentioning
confidence: 99%